PENGARUH KETERLIBATAN KERJA, IKLIM ORGANISASI, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL - Ariana, I Gde Raka; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 7 No 10 (2018)DO - 10.24843/EJMUNUD.2018.v07.i10.p05, 2018)
Organizational commitment is a desire possessed by members of the organization to remain in the organization and one important factor that can contribute to the achievement of organizational goals. This study aims to determine the significant effect of work involvement, organizational climate, and job satisfaction with organizational commitment of restaurant employees in Kerobokan. This research was conducted on the ingka restaurant in Kerobokan. The type of data used is qualitative data sourced from the restaurant overview and quantitative data is the number of employees of the restaurant ingka. The number of respondents is 45 employees. Data collection using observation methods, interviews and questionnaires. Data analysis technique used is multiple linear regression analysis. Based on the results of the analysis found that the involvement of work has a positive and significant impact on organizational commitment, organizational climate has a positive and significant impact on organizational commitment, and job satisfaction has a positive and significant impact on organizational commitment.